INFLUENCE OF CARDIAC AUTONOMIC NEUROPATHY IN RELATION WITH HBA1C VALUES: A PROSPECTIVE CROSS-SECTIONAL STUDY. - Chakraborty, Amit (Student’s Journal of Health Research Africa, 2024)
Background One common adverse effect of diabetes mellitus (DM) is cardiac autonomic neuropathy (CAN), affecting cardiovascular function and is often linked to poor glycemic control, as measured by hemoglobin A1c (HbA1c) values. This study investigates the association between CAN and HbA1c variability, predicts CAN development and progression based on HbA1c levels, and assesses the impact of glycemic control on autonomic dysfunction in DM patients. Methods A prospective study was carried out involving 100 Type 2 DM patients. Inclusion criteria included age ≥18 years, Type 2 DM duration ≥10 years, and ≥4 HbA1c measurements. CAN was evaluated using the Cardiovascular Autonomic Score Scale (CASS). Descriptive statistics, logistic regression, correlation analysis, and multiple linear regression analysis were used for data analysis. Results Participants averaged 58 years old, 60% male and 40% female. There were significant variations in CA parameters between patients with and without CAN (p < 0.001). Factors like mean HbA1c, adjusted HbA1c standard deviation, BMI, duration of DM, hypertension, coronary artery disease, and diabetic retinopathy strongly correlated with composite autonomic scoring (OR 1.32, p < 0.001). High HbA1c variability also indicated CAN onset and progression. Autonomic dysfunction decreased with better glycemic management. Conclusion The study shows that cardiovascular risk factors and glycaemic control are crucial to CAN incidence and progression in Type 2 DM patients. Age, DM duration, BMI, hypertension, and coronary artery disease were strongly linked with higher composite autonomic scores, indicating more severe autonomic neuropathy. To slow CAN progression in this cohort, intensive glycaemic control is needed. Recommendations Intensive glycemic management and targeted interventions addressing cardiovascular risk factors are recommended to mitigate CAN risks and improve outcomes in Type 2 DM patients.